2007
DOI: 10.17221/2058-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Commercial phenotypic tests (API 20E) in diagnosis of fish bacteria: a review

Abstract: ABSTRACT:The available data concerning rapid identification of fish bacteria via commercial phenotypic tests demonstrate that there is no agreement regarding the choice of the tests. However, API 20E, an identification system for Enterobacteriaceae and other non-fastidious Gram-negative rods developed for clinical specimens, seems to be increasingly used for the identification of fish pathogens. In this review, adaptation of API 20E for fish bacterial isolates and its distinctiveness for fish bacteria was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 26 publications
0
28
1
9
Order By: Relevance
“…In our study we confirmed those findings because only about 3 different isolates per fish sample were proved (Table 1). The insufficiency of commercial systems, when testing environmental samples, has been discussed by several authors, and was reviewed by Popovic et al (2007). As apparent, our study does not support the mentioned data and we have demonstrated that both used identification kits have been applicable for reliable identification of enteric bacteria from the normal intestinal bacterial flora in seawater fish.…”
Section: Discussioncontrasting
confidence: 73%
“…In our study we confirmed those findings because only about 3 different isolates per fish sample were proved (Table 1). The insufficiency of commercial systems, when testing environmental samples, has been discussed by several authors, and was reviewed by Popovic et al (2007). As apparent, our study does not support the mentioned data and we have demonstrated that both used identification kits have been applicable for reliable identification of enteric bacteria from the normal intestinal bacterial flora in seawater fish.…”
Section: Discussioncontrasting
confidence: 73%
“…The use of API 20E as a diagnostic tool for aquatic bacteria has been debated for decades, as reviewed by Popovic et al (2007). According to Alsina & Blanch (1994), this could be a useful tool when adjustments or modifications to the manufacturer manual are being made and as a supplement to other methods of identification.…”
Section: Discussionmentioning
confidence: 99%
“…2) according to the degrees of association (Donohue et al, 2006;Eddabra et al, 2012). Although designed primarily for clinical specimens, API 20E has found its way in identification of environmental isolates, particularly fish bacterial isolates (Topic Popovic et al, 2007). However, MALDI TOF MS was found a vastly superior alternative to API 20E in identification and classification of aeromonads from water, sludge and fish samples, capable for differentiation of closely related Aeromonas spp.…”
Section: Methodological Differences In Strain Discriminationmentioning
confidence: 99%
“…The API 20E (bioMerieux, Marcy l'Etoile, France) tests were performed according to the manufacturer's instructions with a few alterations in order to adapt the system to the bacteria of freshwater fish: the incubation time was increased to 48-72 h; the incubation temperature was lowered to 22°C; only the fermentation of sugars was allowed by sealing the cups with sterile mineral oil in the carbohydrate tests (Topic Popovic et al, 2007). A seven-digit profile was obtained for every tested isolate and identified by the Apiweb software.…”
Section: Microbiological Analysesmentioning
confidence: 99%